2017
DOI: 10.18203/2349-2902.isj20170937
|View full text |Cite
|
Sign up to set email alerts
|

A study on diabetic foot and its association with peripheral artery disease

Abstract: Background: Diabetes mellitus is characterized by high blood sugar levels over a prolonged period due to alteration in either the insulin secretion, insulin action, or both. Worldwide, as of the recent 2016 data collected from the World Health Organization (WHO) around 422 million adults have diabetes mellitus which is estimated to almost double by 2030 which is composed of mainly type 2 diabetes (85-90% of all cases). The early detection of peripheral artery disease in asymptomatic patients goes a long way in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Diabetes also increases the risk of amputation for patients dealing with high blood pressure-induced peripheral artery disease, which is caused by a narrowing of the artery and reduction of blood flow [1]. Other conditions such as stroke or coronary, renal, and pulmonary disease can result from blood pressure dysregulation, reduction of blood flow, and vascular occlusion [25]. Over 370 million people worldwide suffer from diabetes and costs related to cardiovascular disease and stroke is currently >$300 billion annually and will exceed $1 trillion by 2035 [6, 7].…”
Section: Clinical Significance Of Vascular Progenitor Cellsmentioning
confidence: 99%
“…Diabetes also increases the risk of amputation for patients dealing with high blood pressure-induced peripheral artery disease, which is caused by a narrowing of the artery and reduction of blood flow [1]. Other conditions such as stroke or coronary, renal, and pulmonary disease can result from blood pressure dysregulation, reduction of blood flow, and vascular occlusion [25]. Over 370 million people worldwide suffer from diabetes and costs related to cardiovascular disease and stroke is currently >$300 billion annually and will exceed $1 trillion by 2035 [6, 7].…”
Section: Clinical Significance Of Vascular Progenitor Cellsmentioning
confidence: 99%
“…11 Another study reported that the prevalence of PAD in cases with diabetic foot syndrome was 38%, as PAD was diagnosed in 57 out of 150 included cases. 12 Aljarid et al 6 also reported that PAD had a prevalence of 32.2% in the included diabetic population. 6…”
Section: Discussionmentioning
confidence: 93%
“…Another study reported that amputation was required in 49.12% of diabetic foot with PAD. 4,12 The presence of PAD has been confirmed as a significant risk factor for amputations in the diabetic population. 29,30 PAD will eventually lead to poor perfusion, delayed wound healing, and increased susceptibility to infections.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the endothelium will show signs of reduced local angiogenesis, endocrine cell proliferation, basement membrane thickness, blood viscosity, changes in microvascular sound, and antioxidant potential. It might also show signs of reduced smooth muscle cell proliferation [ 31 ].…”
Section: Pathophysiology Of Dfusmentioning
confidence: 99%